Keggin-type polyoxometalate-based crown ether complex for lithium–sulfur batteries. Issue 6 (23rd December 2022) - Yang, Guang; Wu, Yuchao; Lv, Zengxiang; Jiang, Xinyuan; Shi, Jianhang; Zhang, Yuzhen; Chen, Ming; Ni, Lubin; Diao, Guowang; Wei, Yongge
Abstract : A novel supramolecular assembly built from Keggin-type polyoxometalates and [18]crown-6 ether building blocks was first applied as sulfur host in lithium–sulfur batteries to resolve remaining critical challenge of polysulfide shuttle effect. Abstract : A novel supramolecular complex Li3 Cl[(HPW12 O40 )(H24 C12 O6 )3 (CH3 CN)2 ] CR-PW12 was confirmed first to apply as a sulfur host in lithium–sulfur batteries. The CR-PW12 @S cathode exhibits a reversible capacity of 1120 mA h g −1 at 1.0 C and excellent cycle stability.